The Outcome of Allogeneic Hematopoietic Stem Cell Transplantation From Different Donors in Recipients With Mucopolysaccharidosis - Qu, Yuhua; Liu, Hao; Wei, Likun; Nie, Shushan; Ding, Wenjiao; Liu, Sha; Liu, Haiyan; Jiang, Hua (Frontiers in Pediatrics, 2022)
There is limited information regarding hematopoietic stem cell transplantation (HSCT) for mucopolysaccharidosis (MPS) IV and VI. This study examined the full donor chimerism, specific lysosomal enzyme levels, and the survival of different MPS children after HSCT from various donor sources and compared the prognosis. A total of 42 children with MPS underwent HSCT, 9 cases were type I, 14 were type II, 15 were type IV, and 4 were type VI. A total of 24 patients received peripheral blood stem cells (PBSC) and 18 patients received umbilical cord blood (UCB). Patients who received PBSC were conditioned with intravenous (IV) busulfan every 6 h for a total of 16 doses, IV cyclophosphamide (CY, 200 mg/kg), and antihuman thymocyte globulin (ATG, 10 mg/kg). While conditioning regimen of patients who received UCB was adjusted to ATG (preposed, pre-) + busulfan + fludarabine + Cy, which includes IV ATG (pre-, 6 mg/kg), IV busulfan every 6 h for a total of 16 doses, IV fludarabine (200 mg/m2) and CY (200 mg/kg). Also, 95.2% (40 of 42) of patients achieved full donor chimerism, and all patients’ specific lysosomal enzyme levels reached normal. The estimated overall survival (OS) at 1 year was 92.9%. There was no significant difference in 1-year OS between patients who received PBSC transplantation and those who received UCB grafts (87.5% vs. 100%, p = 0.0247). The incidence of acute and chronic GVHD did not differ between them. The incidences of pneumonia in PBSC recipients and UCB recipients were 45.8 and 33.3%, respectively, but there few patients suffering from respiratory failure (4.2 and 5.6%, respectively) due to pneumonia. The incidence of cytomegaloviremia was also high in both groups, 58.3 and 44.4% respectively, However, no patient developed CMV disease. All deaths (3 of 42) occurred in patients receiving PBSC grafts, and there was no death in patients receiving UCB grafts. There was no death after transplantation in patients with MPS IV and VI. In addition, respiratory and nervous system functions were improved, whereas valvular heart disease was improved in some patients but progressed in more patients after transplantation. In summary, HSCT is a good therapeutic option for MPS, not only for patients with MPS I or II but also for those with MPS IV or VI. The specific lysosomal enzyme levels can be completely restored to normal, which is the basis for patients to resolve a broad range of clinical outcomes. Moreover, UCB with suitable HLA (HLA-match above 7/10 and 4/6) is a suitable donor source for MPS. Patients who underwent UCB transplantation using the conditioning regimen ATG (pre-) + busulfan + fludarabine + Cy can achieve a higher proportion of full donor chimerism and survival with less severe complications. HSCT can improve organs function in patients with MPS, but it is still worth exploring.